Research on Row Spacing and Sowing Period Influence on Rapeseed Production Parameters - Dan-Laurențiu SUCIU; Cristina MOLDOVAN; Alexandru D. COSTIN; Vasile HORGA; Matei-Marcel DUDA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture)
Rapeseed (Brassica napus L.), is an important annual species from the Brassicaceae family, being related to plants such as mustard, broccoli, cauliflower and cabbage. It is a plant with uses in various fields, especially in oil production. The study was carried out at the Jucu plant station in Cluj County. Two canola cultivation parameters were considered: row spacing and sowing time. The impact of these two characteristics was studied on rapeseed growth and development. Row spacing was established using the following intervals: 25 cm, 37.5 cm and 50 cm. A McCormick Cmax100 tractor with 3-body reversible Vogel plow and Kverneland rotary harrow was used to prepare the seedbed. Sowing was done with the Winterstaiger experimental seeder in three periods: August 20, August 30 and September 10. All data were collected and presented statistically in tables. Branch number, plant height and silique mass were influenced by row spacing and sowing time.